A comparative techno-economic and quantitative risk analysis of hydrogen delivery infrastructure options. (19th April 2021) - Lee, Younggeun; Lee, Ung; Kim, Kyeongsu
Abstract: The comparative techno-economic analysis and quantitative risk analysis (QRA) of the hydrogen delivery infrastructure covering the national hydrogen demands are presented to obtain a comprehensive understanding of the infrastructure of commercial hydrogen delivery. The cost calculation model, which was based on the hydrogen delivery scenario analysis model (HDSAM), was employed to estimate the costs of hydrogen fuel delivery in Seoul, Korea, whose area is small enough to not require intermediate delivery stations. The QRA methodology was modified to be suitable for the comparative analysis of the whole hydrogen infrastructure. The capacities of a hydrogen refueling station and the hydrogen market penetration were employed as the main variables and the two scenarios, viz. the gaseous and liquid hydrogen delivery options, were considered. The analysis results indicate that the delivery system of gaseous hydrogen was superior in terms of cost and that of liquid hydrogen was superior in terms of safety. Both delivery options were affected by the capacity of the station and the market penetration, and the cost and risk drastically changed, especially when the two variables were small. Thus, according to the results, the economic and safety issues of the hydrogen delivery infrastructure are critical to achieving a hydrogen energy society. Highlights: A comprehensive analysis of hydrogen delivery infrastructure was performed. Both cost and risk of hydrogen delivery infrastructure installation were considered. Hydrogen delivery scenario analysis model and modified quantitative risk analysis were employed. Phase of hydrogen and refueling station capacity were considered as the parameter of the analysis.